(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In the article the author analyzes ethnical cultural, ethnical philosophical content of the world conception of the ancient Turks on the basis of semiotic representation of the ethnical concept of ‘Human being’ in the context of common humanity values.